Payment Terminal Emulator - Liudmila Kisialiova (2020)
Nowadays, cash payments are becoming less popular and few understand, what a complicated process stands behind the habitual inserting the card into PoS (Point-of-Sale) terminal. This payment process are implemented by FinTech companies, that provide banks and merchants with ready-to-use PoS terminals. And the most expensive and time-consuming phase of payment solution integration is is the certification of terminal software. In this work we consider communication protocol between a smart card and a PoS terminal based on EMV (Europay Mastercard Visa) international standard, together with its known vulnerabilities. In order to improve the certification process in one Portuguese FinTech company, standalone software for emulation of full EMV transaction workflow is suggested. We present details about implementation of 3C Emulator application.